Extracorporeal shock wave lithotripsy of renal pelvis Stones with PCK stonelith lithotripter - (:unkn) unknown (My University, 2005)
Shock wave lithotripsy (SWL) has made a revolution in the treatment of urolithiasis. It is a safe procedure with a lower morbidity than open surgery or percutaneous nefrolithotomy (PCN) [Brannen GE, Bush WH, Correa RJ et al., J Urol 1985; 133: 6 and Lingeman JE, Newman D, Mertz JHO et al., J UROL 1986; 135: 1134]. In this article, we analyze our results of SWL with PCK Stonelith-V5 Lithotripter for the renal pelvis localized stones. About 97 patients with radiopaque stone localized in the renal pelvis were treated with PCK lithotripter from January 2001 to March 2003. The study group was divided into two groups according to their stone size. The stone size was ≤ 10 mm in the first group and 11-20 mm in the second group. 56(57) patients were male and 41 (43) were female. Age range was 7-68 (mean 44) years. The overall success rates of SWL for the treatment of renal pelvic stones in our study group was 35 and 62.2 for stones 10 mm or less and 11-20 mm, respectively. Since the focal zone is 7.7 × 30 mm, the stones can easily get out of the focal zone area with respiration and as a result, the success rate is decreased. So, general anesthesia can be preferred for the treatment of stones ≤10 mm with the PCK Stonelith Lithotripter. © Springer 2005.
Keywords: Lithotripsy; Renal pelvis; Shock wave; Stone; Urolithiasis